Literature Review : Kualitas Laporan Keuangan Pada Badan Usaha Milik Desa (Bumdes) Di Indonesia - Anita Firnanda (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
This Literature Review aims to map research on the quality of BUMDes financial reports in Indonesia. This research method uses Literature Review (Data analysis by mapping 14 selected journals from 2018 to 2023 in the Google Scholar database. The results of this study indicate factors that affect the quality of local government financial reports in Indonesia, namely: The quality of financial statements, accounting understanding, village-owned enterprises, accounting information technology, training, education level and human resource competencies and employee performance. This study also shows that quality financial reports must be accountable and transparent. Financial reporting has a significant influence on the quality of financial reporting of village-owned enterprises in Indonesia.